2015
DOI: 10.1038/gt.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

Lister strain vaccinia virus with thymidine kinase gene deletion is a tractable platform for development of a new generation of oncolytic virus

Abstract: Vaccinia virus (VV) has many attractive characteristics as a potential cancer therapeutic. There are several strains of VV. The nonvaccine strain Western Reserve VV with deletion of both the thymidine kinase and the viral growth factor genes (known as WRDD) has been reported as the most potent tumor-targeted oncolytic VV. Other strains, such as the European vaccine Lister strain, are largely untested. This study evaluated the antitumor potency and biodistribution of different VV strains using in vitro and in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…6 In addition, VV-based OV therapies have strong potential within the framework of postsurgical immune restoration because in addition to the attributes of OV discussed, we have shown that VV entry into tumor cells is facilitated by vascular endothelial growth factor, 10 levels of which are elevated following surgical stress. 11 Given the role of NK cells in containing disease, in particular targeting tumor cell populations that are refractory to adaptive immune control via MHCI suppression, and reducing postoperative morbidity, we sought to rationally redesign our thymidine kinase (TK)-deleted Lister strain VV, Vaccinia Virus Lister 15 (VVL15) 12 to interrupt naturally evolved viral mechanisms of antiviral NK cell suppression with a view to creating a more powerful vector for primary treatment of cancers and additionally optimized as a neoadjuvant therapy. The VV N1L protein is a 13.8 KDa, non-essential virulence determinant 13 and plays an important role in immune evasion via inhibition of cellular inflammatory pathways and early innate immune responses against viral infection, in particular NK cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, VV-based OV therapies have strong potential within the framework of postsurgical immune restoration because in addition to the attributes of OV discussed, we have shown that VV entry into tumor cells is facilitated by vascular endothelial growth factor, 10 levels of which are elevated following surgical stress. 11 Given the role of NK cells in containing disease, in particular targeting tumor cell populations that are refractory to adaptive immune control via MHCI suppression, and reducing postoperative morbidity, we sought to rationally redesign our thymidine kinase (TK)-deleted Lister strain VV, Vaccinia Virus Lister 15 (VVL15) 12 to interrupt naturally evolved viral mechanisms of antiviral NK cell suppression with a view to creating a more powerful vector for primary treatment of cancers and additionally optimized as a neoadjuvant therapy. The VV N1L protein is a 13.8 KDa, non-essential virulence determinant 13 and plays an important role in immune evasion via inhibition of cellular inflammatory pathways and early innate immune responses against viral infection, in particular NK cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…The Lister strain virus with Thymidine Kinase gene deletion (VVΔTK) demonstrated superior antitumor potency and cancer-selective replication in vitro and in vivo, compared with WRDD, especially in human cancer cell lines and immune-competent hosts. Further investigation of functional mechanisms revealed that Lister VVΔTK presented favorable viral biodistribution within the tumors, with lower levels of proinflammatory cytokines compared with WRDD, suggesting that Lister strain may induce a diminished host inflammatory response [105]. Our comprehensive study indicates that the Lister strain VV with TK deletion is a particularly promising VV strain for the development of the next generation of tumor-targeted oncolytic therapeutics.…”
Section: Future Perspectivementioning
confidence: 81%
“…We note that there are also other types of theranostic agents utilizing different biological sentinel systems, including viruses and bacteria. For example, viruses can be engineered to become capable of replicating only in cancer cells (oncolytic viruses) by deleting factors that are essential for viral replication in normal cells but not cancer cells (such as thymidine kinase [46][47][48]), or to become capable of exerting their functions only in target cells by introducing cell-specific promoters [49,50,50]. Certain types of bacteria can also be directed to accumulate at cancer sites by utilizing their anaerobic or chemotactic properties [51,52] or by engineering their quorum-sensing properties [53].…”
Section: Discussionmentioning
confidence: 99%